Mentoring of Batik Tulis Techniques for Jerukgamping Village Youth: Cultivating Interest in Culture-Based Entrepreneurship - Sumartini Rahaju (Future Tecno-Science Publisher, 2025)
This study aims to analyze the effectiveness of batik tulis mentoring in fostering cultural-based entrepreneurship among teenagers in Jerukgamping Village, Sidoarjo. Using the Asset-Based Community Development (ABCD) Method, this research focuses on leveraging local assets as the foundation for training and creative economic empowerment. This approach emphasizes the strengths and potential of local communities in supporting youth skill development in batik tulis craftsmanship. Literature review findings indicate that asset-based mentoring programs enhance teenagers’ technical skills in batik production while raising awareness of the cultural values embedded in traditional batik. Additionally, training helps them identify business opportunities and understand digital-based marketing strategies. Key success factors include community support, access to local resources, and the involvement of experienced mentors. The study concludes that an asset-based approach in batik tulis mentoring has the potential to strengthen creative economic sustainability, preserve local heritage, and increase youth participation in cultural entrepreneurship.